CÁC KIỂU TRƯỢT LỞ KHU VỰC CỐC PÀI HUYỆN XÍN MẦN TỈNH HÀ GIANG - Thơm, Bùi Văn (Vietnam Journal of Earth Sciences, 2012)
Types of landslides in the Coc Pai area, Xin Man District, Ha Giang provinces The survey and research results in the Coc Pai area, Xin Man district, Ha Giang province, has identified four types of landslide with different characteristics as followed: 1. Mixture slide occured in all soil types (rock, weathered crust), slope steepness of 25-70° and the transition between two places where the terrain is steep. The sliding blocks are the arc form, progressive with equal length and width. 2. Flow slide occurred in the slope of deluvium on the cone area with length (200-300m), width (50-150m), slope steepness of 10°-20°. The volume of slide block about from tens to thousands cubic meters. 3. Stream slide occured in the completely weathered and uncompletely weathered crust, along streams of type 1 with length (200-500m) of many times more than their width (30-50m), slope steepness of 10°-20°. The mud flow is usually accompanied with this types. 4. The falls, occurring mainly in the rocks that were broken up and uncompletely weathering crust, slopes with gradients >50°. This is the first phase of the next type of landslide, flood and mud flow or flash flood. Among the four types, flow slide and stream slide often occur in large-scale over a greater length and it is difficult to detect them immediately, causing unexpected factors and very high risk.